Implication of miRNA in the diagnosis and treatment of breast cancer. Issue 8 (August 2011) - Castañeda, Carlos A; Agullo-Ortuño, María Teresa; Fresno Vara, Juan Angel; Cortes-Funes, Hernan; Gomez, Henry L; Ciruelos, Eva
Breast cancer (BC) comprises a group of different diseases characterized by changes in tissue structure and gene expression. Recent advances in molecular biology have shed new light on the participation of genes and their products in the biology of BC. MicroRNAs (miRNAs) are small noncoding endogenous RNA molecules that appear to modulate the expression of more than a third of human genes, and their implications in cancer have grasped the attention of the scientific community. Recently, several studies have described the association between miRNA expression profiles and pathological and clinical BC features. Moreover, these molecules represent a new type of molecular marker that can identify prognosis and guide the management of BC patients. With the increasing understanding of miRNA networks and their impact in the biology of BC, as well as the development of viable strategies to modulate specific miRNAs, we could improve the treatment of this disease.